CYP2D6 gene polymorphisms in Brazilian patients with breast cancer treated with adjuvant tamoxifen and its association with disease recurrence - Melo, Mariella De Ameida; De Vasconcelos-Valenca, Rodrigo Jose; Neto, Fidelis Manes; Borges, Rafael Soares; Costa-Silva, Danylo Rafhael; Barros-Oliveira, Maria Da Conceicao; Borges, Umbelina Soares; Alencar, Airlane Pereira [UNESP]; Silva, Vladimir Costa; Da Silva, Benedito Borges (Spandidos Publ Ltd, 2016)
At present, there is controversy regarding the efficacy of tamoxifen in breast cancer patients who are carriers of cytochrome P450 2D6 (CYP2D6) gene polymorphisms, in terms of recurrence and overall survival. Thus, the aim of the present study was to investigate the association of the CYP2D6 *4, *10 and *17 gene polymorphisms with breast cancer recurrence in a Brazilian population. The cohort comprised 40 receptor-positive breast cancer patients without recurrence and 40 with distant recurrence. A 3-ml sample of peripheral blood was collected from each patient to determine the presence of the *4, *10 and *17 single nucleotide polymorphisms of the CYP2D6 gene by quantitative polymerase chain reaction analysis. There was no statistically significant difference between the two groups regarding the polymorphism frequency (P= 0.246). The results revealed that intermediate metabolizers occurred in 5% of patients without recurrence and in 15% of those with distant recurrence. Poor metabolizers occurred in only 1 patient (2.5%) per group, and there was no significant difference between the groups (P= 0.789). The present study concluded that the CYP2D6 gene polymorphism in women with hormone-sensitive breast cancer treated with tamoxifen was not associated with disease recurrence.
Keywords: breast cancer; cytochrome P450 2D6 gene; polymorphism; tamoxifen; recurrence